Climate smart agriculture? Adaptation strategies of traditional agriculture to climate change in sub-Saharan Africa - Okoronkwo, David John; Ozioko, Remigius Ikechukwu; Ugwoke, Rachael Ujunwa; Nwagbo, Uzoh Victor; Nwobodo, Cynthia; Ugwu, Chidiebere Happiness; Okoro, Gozie Godswill; Mbah, Esther C. (Frontiers in Climate, 2024)
Sub-Saharan Africa faces increasingly unpredictable and extreme weather patterns due to climate change, posing significant threats to food security and rural livelihoods. Traditional agriculture, deeply rooted in the region's history and culture, is particularly vulnerable to these changes. This study investigates the adaptation strategies of traditional agricultural farmers to climate change using southeast Nigeria as a microcosm of the broader challenges facing sub-Saharan Africa. Multistage sampling procedure was used to select 75 farmer group leaders in the study region. Cross-sectional data were collected through semi-structured interview schedules and focus group discussions. Data were analyzed using descriptive statistics and principal component analysis using Varimax rotated matrix. Findings showed that farmers rely on face-to-face discussions with neighbours (76.0%), fellow farmers (66.7%), and radio (54.7%) as their primary sources of information on climate change. Results showed that traditional adaptation practices such as use of organic manure (x ̅ = 3.89), traditional organic composting (x ̅ = 3.80), afforestation (x ̅ = 3.71), agroforestry (x ̅ = 3.61) were the topmost traditional agricultural practices use to cushion the effect of climate change. Conserving the overall soil health, soil moisture retention, reducing CO2 emissions and maintaining crop productivity were the major reasons for using the traditional approaches. Climate-induced drought and high cost of accessing weather information (x ̅ = 1.93), and inadequate funding (x ̅ = 1.92), among others were the key constraints to adaptation. Results showed that farmers prioritize agronomic manipulation and integrated research approaches as key strategies to adapting traditional agriculture to climate anomalies. Although farmers used their indigenous practices, continuous learning and improvement through capacity-building workshops and progress monitoring are essential for effective climate change adaptation. Policymakers should invest in promoting indigenous knowledge, provide access to credit for climate-resilient infrastructure, promote climate-smart agricultural practices and foster collaborative research as the cornerstone for sustainable rural development.